Non-invasive methods to evaluate liver fibrosis in patients with non-alcoholic fatty liver disease - Wang, Jincheng; Qin, Tao; Sun, Jinyu; Li, Shiwu; Cao, Lihua; Lu, Xiaojie (Frontiers in Physiology, 2022)
Nonalcoholic Fatty Liver Disease (NAFLD) is a chronic liver disease strongly related to insulin resistance and metabolic syndrome, which has become the most common liver disorder in developed countries. NAFLD embraces the full pathological process of conditions from steatosis, nonalcoholic steatohepatitis, and finally, cirrhosis. The progress of NAFLD will lead to increasingly severe symptoms with the level of fibrosis developing. Therefore, evaluating the fibrosis stage is crucial for patients with NAFLD. Liver biopsy is currently considered the gold standard for staging fibrosis. However, due to the limitations of liver biopsy, noninvasive alternatives were majorly studied and validated in patients with NAFLD. The advantages of noninvasive methods include their high safety and convenience compared with other invasive approaches. This review introduces the noninvasive methods, summarizes their benefits and limitations, and assesses their diagnostic performances for NAFLD-induced fibrosis.